Leucaena leucocephala as treatment for ascariasis and trichuriasis: a cost effectiveness analysis - TJIPTO RINI; YUSMANIAR; KUAT PRABOWO (International Journal of Pharma and Bio Sciences, 2017)
The purpose of this study was to evaluate the possibility of using Leucaena leucocephala seed – an herbal drug, instead of Pyrantel Pamoate as an attempt to heal worm-infected children. A total number of 80 worm-infected children were treated either by Pyrantel Pamoate 250 milligrams single dose (20 children) or by Leucaena leucocephala seed (60 children) with different doses – single dose per day, single dose for two (2) consecutive days and single dose for three (3) consecutive days. The results showed that after three months of treatment either by Pyrantel Pamoate or Leucaena leucocephala all worm-infected children were cured indicated by the absence of Ascaris lumbricoides and Trichuris trichiura eggs in their faeces except for those who were treated by a single dose per day of Leucaena leucocephala whose recovery rate was only 80%. Further analysis to find out which treatment is the most effective economically, this study by using Cost-Effectiveness Analysis (CEA) found that healing worm-infected children by Leucaena leucocephala with single dose for two (2) consecutive days is the most effective one. Based on simple survey, this study also showed that the level of acceptance to using this herbal drug is high. Using Leucaena leucocephala as an alternative treatment, therefore is suggested.